Pengaruh E Modul Berbasis Canva terhadap Hasil Belajar Siswa pada Mata Pelajaran SKI di MTsN 1 Lima Puluh Kota - Syifa Urrahmah; Puti Andam Dewi (YASIN, 2026)
The use of digital teaching materials is an alternative for improving the quality of the learning process and outcomes in Islamic Cultural History (SKI). However, studies on the use of Canva-based e-modules for the Umayyad Caliphate topic at the Islamic junior secondary school level remain limited. This study aimed to analyze the effect of using a Canva-based e-module on students’ learning outcomes in SKI at MTsN 1 Lima Puluh Kota. This study employed a quantitative approach with a quasi-experimental nonequivalent control group design. The sample comprised 60 students: 30 students from Grade VII C as the experimental group and 30 students from Grade VII D as the control group, selected through purposive sampling. Data were collected through a pretest, posttest, and documentation and subsequently analyzed using normality, homogeneity, N-gain, and independent-samples t-tests with the assistance of IBM SPSS Statistics version 27. The results showed that the experimental group obtained a mean N-gain of 0.7707, which was classified as high, whereas the control group obtained a mean of 0.5592, which was classified as moderate. The independent-samples t-test indicated a significant difference in learning outcomes between the two groups (p < 0.001). These findings indicate that using a Canva-based e-module produced a greater improvement in SKI learning outcomes than the instruction provided to the control group. This study provides empirical evidence for the development of digital teaching materials in SKI instruction and confirms that Canva-based e-modules can be used as an alternative learning resource for teachers and students. Future research should involve a larger sample and a longer intervention period to strengthen the generalizability of the findings.